THE SOCIO-ECONOMIC CONSEQUENCES OF THE LAKE THE CASE STUDY OF KINASSEROM VILLAGE IN THE LAKE NOMIC CONSEQUENCES OF THE LAKE CHAD REGRESSION ON THE POPULATION: THE CASE STUDY OF KINASSEROM VILLAGE IN THE LAKE CHAD REGRESSION ON THE POPULATION: THE CASE - HOUNGA, ANTOINE; GBAGUIDI, GBEDOLO ARNAULD GABRIEL; AHODEKON, SESSOU COOVI CYRIAQUE; Fadall-Allah, Doka-Ansé (My University, 2016)
The purpose of this paper is to examine the socio regression on the population of Kinasserom. The causes and the outcome of such a phenomenon on the various activities of the population are the keys point of our inve documentation is used and the analysis of the population points of views confirm our results and interpretatio among the different actors (Protag The purpose of this paper is to examine the socio-economic consequences of the lake Tchad regression on the population of Kinasserom. The causes and the outcome of such a phenomenon on the various activities of the population are the keys point of our inve documentation is used and the analysis of the population points of views confirm our results and interpretations. The regression of the lake chad is caused by the drought, significant year reduction among the different actors (Protagonists). economic consequences of the lake Tchad regression on the population of Kinasserom. The causes and the outcome of such a phenomenon on the various activities of the population are the keys point of our investigations. A specific documentation is used and the analysis of the population points of views confirm our results and chad is caused by the drought, significant year reduction
Keywords: Conflicts; Regression; Fishing products; Population; Consequences.